ANALISIS PENGARUH MANAJEMEN MODAL KERJA, UKURAN PERUSAHAAN, DAN DER TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Consumer goods Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2015) - Sidabutar, Riyandi Bittatar; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2017)
The purpose of this research is to analyze the effect of working capital management (number of days cash turnover, number of days accounts receivable, number of days inventory, and number of days accounts payable), size firm, and DER on profitability (ROA) Consumer Goods companies. The population of this research is the Consumer Goods sector companies listed on the Indonesian Stock Exchange (BEI) in 2012-2015. The sampling method used is purposive sampling and acquired 34 companies in the sample. The analytical method used is multiple regression analysis and using classical assumption test. Based on the results of research conducted, simultaneous number of days cash turnover, number of days accounts receivable, number of days inventory, number of days accounts payable, size firm, and DER effect on profitability (ROA). Then partially, number of days cash turnover, number of days accounts payable, and size firm have positive significant effect on ROA. While the number of days accounts receivable and DER have significant negative effect on ROA. number of days inventory have not significant positive influence on ROA.